Amṡāl Muṣarraḥah dalam Surat Al-Baqarah [2]:17-18 (Studi Analisis Leksikal, Diksional Dan Stilistika) - Tsauri, Sidiq Samsi; Fitriana, Muhammad Azizan; Haq, M. Ziyadul (ZAD Al-Mufassirin, 2023)
This study aims to analyze the use of amṡāl muṣarraḥah in Surat Al-Baqarah [2]:17-18 and its resulting implications on the meaning of lexical, dictional and stylistic selection of lafadz. The research method used is analytic descriptive qualitative with the approach used linguistic approaches and history. The conclusion of this study is, first: Lafadz in the amṡāl muṣarraḥah of the Qur'an has a very important role in knowing the interpretation in general. Second: there is a strong relationship between the choice of words in diction and the resulting meaning so as to produce a beautiful and fluent style that is impossible to represent by other words lexically. Third: stilistics in amṡāl are divided into two in lafadz or expression (style), both of which have implications on the aspect of meaning that will be produced so as to facilitate a reader in understanding it, obeying it and practicing it as desired by Allāh subhānahū wata'āla.